HUBUNGAN KEPATUHAN MENJALANKAN PROTOKOL KESEHATAN PANDEMI COVID - 19 DENGAN PENGETAHUAN COVID - 19 DAN PERSEPSI COVID-19 PERAWAT DI RS AVICENNA BIREUEN, KOTA BIREUEN ACEH - WIDYA AFIFAH; DES SURYANI; IKHFANA SYAFINA; IKA NOPA (LP2MTBM MAKARIOZ, 2021)
Coronavirus Disease 2019 (COVID-19) is a respiratory disease caused by Severe Acute Respiratory Disease SyndromeCoronavirus-2 (SARS-CoV-2). Health workforce efforts to break the chain of virus transmission in Health Service Facilities.Therefore it is very important to apply knowledge and perceptions of transmission of COVID-19. Some literature states thatthere is a relationship between one's compliance with knowledge and perception. However, other researchers said there wasno linkage of deficiencies, so researchers wanted to see which one was most appropriate about this. To determine therelationship between nurses' compliance implementing COVID-19 Pandemic Health Protocol with COVID-19 knowledgedand perception of COVID-19.. Caterogical analysis using cross sectional design. Nurses working at Avicenna Bireuen Hospitalin 2020. The research data were obtained from primary data using a COVID-19 Health Protocol compliance questionnaire,knowledge and perception questionnaire of COVID-19. Then do to analysis with the Chi Square test. The results of ChiSquare test showed that there was a significant relationship between nurses' compliance implementing COVID-19 pandemichealth protocol with knowledge of COVID- 19 wih a value of P=0.004 (p<0.05) and perceptions of COVID-19 with a value ofP=0.012 (p<0.05). Nurses who adhere to the COVID-19 pandemic health protocol have good knowledge of COVID-19 andgood perceptions of COVID-19.